Morphological changes of the distal femur growth plate of rabbits under bilateral temporal block using non-locking plates and screws - Khmyzov, Sergey; Rokutov, Victor; Iershov, Dmytro; Ashukina, Nataliya; Danyshchuk, Zinaida; Maltseva, Valentyna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
For the treatment of the moderate leg length discrepancy (2–6 cm) in children surgeons use temporal growth plate (GP or epiphyseal cartilage) block with plates and screws. Objective: to study morphological changes in distal femur growth plate of rabbits under bilateral temporal block with non-locking plates and screws. Methods: we blocked distal GP of the right femur of 9 rabbits (8 weeks old). On 3rd, 5th and 7th weeks histological study of the distal femoral growth plate of both femurs with morphometry was made. Results: in 3rd weeks after surgery the height of the GP on the operated side was decreased in lateral and medial parts in 2.06 and 1.98 times (p < 0.001), in central — conversely — increased in 1.18 times (p < 0.001) compare to contralateral limb. In 5th weeks in the whole GP structural changes were noted. Height of the GP was decreased comparing to contralateral limb in the lateral side in 1.3 times (p < 0.001), in the medial part — in 1.14 (p < 0.01) times. On 7th week destructive changes in the GP progressed, its height was decreased comparing to contralateral limb in the lateral part in 3.29 times, in the medial — in 3.5 times (p < 0.001). Conclusions: on 3rd, 5th, 7th weeks after bilateral distal femur GP block in rabbits we have found all typical zones. Destructive changes (histoarchitecture disorder, cells density etc.) progressed during the time of experiment. The height of the operated distal femoral GP and area of the primary osteogenesis was decreased comparing to the contralateral kimb with longer follow-up period. It indicates an inhibition of the longitudinal bone growth.